PENGARUH PENGERING AEROSIL DAN KROSPOVIDON TERHADAP KARAKTERISTIK FISIK SOLID-SELF NANOEMULSIFYING DRUG DELIVERY SYSTEM KURKUMIN - Wahyuningsih, Iis; Kyllingga, Muhammad Rhapis (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
Curcumin belongs to BCS II with low solubility but high permeability. In previous studies, a curcumin SNEDDS formulation was developed with a curcumin concentration of 7 mg/mL, VCO (11%), Tween 80 (65.66%), and PEG 400 (23.34%); however, this formulation had the drawback of being incompatible with capsule shells. The objective of this study was to formulate and characterise solid SNEDDS curcumin using aerosil and crospovidone as drying agents. The S-SNEDDS formulation was prepared using the absorption-to-solid carrier method with aerosil and crospovidone as drying agents, followed by characterisation using parameters such as clarity, emulsification time, static angle test, bulk density, tapped density, Carr’s index, Hausner ratio, and droplet measurement. The resulting S-SNEDDS curcumin formulations contained 0.5 g of aerosil drying agent per mL and 3 g of crospovidone. The formulations exhibited the following characteristics: clarity of 96.28±0.00% and 95.35±0.01%, emulsification time of 52.58±0.75 seconds for aerosil in AGF and 56.14±0.42 seconds in distilled water, while crospovidone yielded 48.63±1. 84 seconds and 50.58±0.45 seconds, angle of repose 19.77±2.03º and 41.41±3.35º, bulk density and tapped density 0.56±0.00 and 0.63±0.01 for aerosil, and 0.50±0.00 and 0.57±0. 01 for crospovidone, Carr’s index and Hausner ratio 11.33±2.08% and 1.13±0.03 for aerosil, and 12.66±2.51% and 1.15±0.03 for crospovidone, with droplet sizes of 77.08 nm and 198.2 nm. Aerosil-dried S-SNEDDS produced granules with better characteristics.